Tidal pumping and biogeochemical processes: Dissolution within the tidal capillary fringe of eogenetic coastal carbonates. Issue 11 (4th July 2020) - Gulley, J.D.; Breecker, D.; Covington, M.; Cooperdock, S.; Banner, J.; Moore, P.J.; Noronha, A.; Breithaupt, C.; Martin, J.B.; Jenson, J.
Abstract: Growing evidence suggests microbial respiration of dissolved organic carbon (DOC) may be a principal driver of subsurface dissolution and cave formation in eogenetic carbonate rock. Analyses of samples of vadose zone gasses, and geochemical and hydrological data collected from shallow, uncased wells on San Salvador Island, Bahamas, suggest tidally varying water tables may help fuel microbial respiration and dissolution through oxygenation. Respiration of soil organic carbon transported to water tables generates dysaerobic to anaerobic groundwater, limiting aerobic microbial processes. Positive correlations of carbon dioxide (CO2 ), radon‐222 ( 222 Rn) and water table elevation indicate, however, that tidal pumping of water tables pulls atmospheric air that is rich in oxygen, and low in CO2 and 222 Rn, into contact with the tidal capillary fringe during falling tides. Ratios of CO2 and O2 in vadose gas relative to the atmosphere indicate this atmospheric oxygen fuels respiration within newly‐exposed, wetted bedrock. Deficits of expected CO2 relative to O2 concentrations indicate some respired CO2 is likely removed by carbonate mineral dissolution. Tidal pumping also appears capable of transferring oxygen to the freshwater lens, where it could also contribute to respiration and dissolution; dissolved oxygen concentrations at the water table are at least 5% saturated and decline to anaerobic conditions 1–2 m below. Our results demonstrate how tidal pumping of air to vadose zones can drive mineral dissolution reactions that are focused near water tables and may contribute to the formation of laterally continuous vuggy horizons and potentially caves. © 2020 John Wiley & Sons, Ltd. Abstract : Cave formation in eogenetic limestone is widely cited to be driven by dissolution caused by mixing of fresh and saline groundwater. We show that dissolution instead may be driven by oxygenation and microbial respiration at tidally oscillating water tables. Because dissolution occurs at the locus of respiration, caves in eogenetic limestone may be biogeomorphic in origin.